A Novel Approach for Engagement in Team Training in High-Technology Surgery: The Robotic-Assisted Surgery Olympics. Issue 6 (7th September 2022) - Cohen, Tara N.; Anger, Jennifer T.; Kanji, Falisha F.; Zamudio, Jennifer; DeForest, Elise; Lusk, Connor; Avenido, Ray; Yoshizawa, Christine; Bartkowicz, Stephanie; Nemeth, Lynne S.; Catchpole, Ken
Abstract : Introduction: There is ongoing interest in the development of technical and nontechnical skills in healthcare to improve safety and efficiency; however, barriers to developing and delivering related training programs make them difficult to implement. Unique approaches to training such as "serious games" may offer ways to motivate teams, reinforce skill acquisition, and promote teamwork. Given increased challenges to teamwork in robotic-assisted surgery (RAS), researchers aimed to develop the "RAS Olympics, " a game-based educational competition to improve skills needed to successfully perform RAS. Methods: This pilot study was conducted at an academic medical center in Southern California. Robotic-assisted surgery staff were invited to participate in the "RAS Olympics" to develop their skills and identify opportunities to improve processes. Impact of the activity was assessed using surveys and debriefs. Results: Sixteen operating room team members participated and reacted favorably toward the RAS-Olympics (average score, 4.5/5). They enjoyed the activity, would recommend all staff participate, felt that it was relevant to their work, and believed that they practiced and learned new techniques that would improve their practice. Confidence in skills remained unchanged. Participants preferred the RAS Olympics to traditional training because it provided an interactive learning environment. Conclusions: The successful implementation of the RAS Olympics provided insight into new opportunities to engage surgical staff members while also training technical and nontechnical skills. Furthermore, this shared experience allowed surgical staff members to gain a greater appreciation for their teammates and an understanding of the current challenges and methods to improve teamwork and communication while promoting safety and efficiency in RAS.